Highly Stable Multiresponsive Photonic Hydrogels Based on a Crosslinked Acrylamide-N-Isopropylacrylamide co-Polymer. Issue 200 (24th July 2019) - Chu, Chengyi; Wu, Huangsheng; Sun, Aihua; Tang, Xiaobing; Yan, Yugang; Shao, Guoxiong; Li, Zhixiang; Guo, Jianjun; Xu, Gaojie
Abstract: The multresponsive photonic hydrogels (MRPHs) based on Fe3O4@C NPs and Acrylamide-N-isopropylacrylamide (AM-NIPAM) was prepared by UV polymerization process with the help of magnetic field. This work is mainly about the long-term stability of MRPHs. The mechano-response performance of MRPHs after being remained in water for a year has been measured and discussed in details. The result shows that the MRPHs were still very sensible and exhibit brilliant structure color. The reflectance peak of MRPHs changed markedly (from 700 nm to 550 nm) as increasing compression from 0 to 1N and the structure color change can be made reversible for ∼100 times or even more if necessary. Besides, the structure color of MRPHs was broken after being natural air-dried for 3 months and it can recover when dried MRPHs were immerged in water for 10 hours. So the MRPHs have good stability and the structure color can persevere for long time without fading, which contributes to the piratical application of MRPHs used as sensors.